Communiquer sur l’authenticité d’un patrimoine architectural : le cas du grand ksar de Temacine dans le Sud-Est algérien - Aissa Merah; Ismail Bendebili (Communiquer)
At a time when tourism and/or culture are strongly affected by online information growth, enhancement of architectural sites—in addition classified protected sectors—arises more than ever. How to develop an architectural heritage as “tourism product” while respecting its preservation and authenticity? Through public and territorial communication, we will focus on enhancing the Temacine ksar, located near the Oued Righ in the Algerian Sahara. First, we will analyze the different communication actions of institutions and associations for the preservation and promotion of that heritage site. Then, two aspects of the communication objectives of the heritage of authenticity will be discussed: the creation of meaning and economic value. Finally, we will advocate a communication strategy combining patrimonial and tourist development of cultural heritage.